2008
DOI: 10.1021/bc8004304
|View full text |Cite
|
Sign up to set email alerts
|

Single-Step Azide Introduction in Proteins via an Aqueous Diazo Transfer

Abstract: The controlled introduction of azides in proteins provides targetable handles for selective protein manipulation. We present here an efficient diazo transfer protocol that can be applied in an aqueous solution, leading to the facile introduction of azides in the side chains of lysine residues and at the N-terminus of enzymes, e.g. horseradish peroxidase (HRP) and the red fluorescent protein DsRed. The effective introduction of azides was verified by mass spectrometry, after which the azido-proteins were used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
87
0
3

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 29 publications
1
87
0
3
Order By: Relevance
“…The azide is preferred as the chemical handle because of the high degree of oxidation of the phosphine moiety in aqueous solutions. The azide can be introduced into a protein chemically, that is, by a diazotransfer reaction [39] or biochemically, either by using genetic engineering for the incorporation of azide-containing amino acids into proteins [40] or by post-translational modifications. The latter concept was used in a combined effort by the research groups of Tirrell and Bertozzi.…”
Section: Protein Labelingmentioning
confidence: 99%
“…The azide is preferred as the chemical handle because of the high degree of oxidation of the phosphine moiety in aqueous solutions. The azide can be introduced into a protein chemically, that is, by a diazotransfer reaction [39] or biochemically, either by using genetic engineering for the incorporation of azide-containing amino acids into proteins [40] or by post-translational modifications. The latter concept was used in a combined effort by the research groups of Tirrell and Bertozzi.…”
Section: Protein Labelingmentioning
confidence: 99%
“…Glucose oxidase (GOx) was encapsulated in the interior of these polymersomes and Candida antarctica lipase B (CalB) was incorporated into the vesicle bilayer membranes. Horseradish peroxidase (HRP) was reacted with imidazole-1-sulfonyl azide hydrochloride to introduce azide functionalities to this enzyme [57,58]. The HRP was then conjugated to the outer surface of the polymersomes via click-chemistry.…”
Section: Aminementioning
confidence: 99%
“…Candida antarctica lipase B and its azidefunctionalized counterpart (AHA-CalB) as well as the azidefunctionalized HRP (azido-HRP) and the substrate glucose mono-acetate (1-O-acetyl-D-gluco-pyranose, further denoted as Gluc-Ac), were obtained as described elsewhere. 23,24 Horseradish peroxidase (E.C. 1.11.1.7) type VI and glucose oxidase (E.C.…”
Section: Experimental Section General Materialsmentioning
confidence: 99%
“…GOx was left in solution as it is the ''slowest'' enzyme in sequence. HRP was prepared following literature procedures 24 and coupled with CuAAC to hexynyl-5 0 -AGT ATT GAC CTA AGT ATT GAC-3 0 , under similar conditions as applied for DNA-CalB to obtain DNA-HRP. As previous findings showed that unreacted CalB did not bind to the modified capillaries, the DNA-HRP was only filter dialyzed to remove the excess of unreacted DNA.…”
Section: Three-enzyme Cascade Reactionmentioning
confidence: 99%